ANGI-04. A NOVEL TROY-JAK1 SIGNALING COMPLEX IN GLIOBLASTOMA INVASION. (11th November 2019) - Ding, Zonghui; Kloss, Jean; Tuncali, Serdar; Tran, Nhan; Loftus, Joseph
Abstract: Glioblastoma (GBM) is the most common and deadly malignancy of the central nervous system in adults with a median survival of about 15 months after diagnosis. Its aggressive and highly infiltrative nature renders the current standard treatment of maximal surgical resection, radiation, and chemotherapy relatively ineffective. Identifying the molecular events that regulate GBM migration/invasion is required to develop more effective therapeutic regimens to treat GBM. Expression of TROY, an orphan receptor of the TNFR superfamily, increases with increasing glial tumor grade, inversely correlates with patient survival, stimulates GBM cell invasion in vitro and in vivo, and increases resistance to temozolomide and radiation therapy. Conversely, silencing TROY expression inhibits GBM cell invasion, increases sensitivity to temozolomide, and prolongs survival in a preclinical intracranial xenograft model. Thus, the TROY signaling pathway represents an attractive therapeutic target. We previously reported that increased TROY expression strongly activates NF-kB. We have identified for the first time that TROY forms a unique signaling complex with JAK1. Interaction with TROY stimulates phosphorylation of JAK1 and significantly increases the activation of STAT3. TROY specifically associates with JAK1 as it does not associate with other JAK family members. Co-immunoprecipitation analysis demonstrated that TROY interacts with JAK1 through its cytoplasmic domain as a TROY variant without its extracellular domain associates with JAK1 while a TROY variant without a cytoplasmic domain fails to bind JAK1. Luciferase reporter assay confirmed that full length TROY or a variant lacking the extracellular domain are able to induce STAT3 activation, but not a TROY variant lacking the cytoplasmic domain. Pharmacological inhibition of JAK1 by the FDA approved inhibitor ruxolitinib or knockdown of JAK1 by siRNAs significantly inhibited TROY-induced STAT3 activation and GBM cell migration. Together, our data indicate that the TROY-JAK1 complex represents an unappreciated therapeutic target to inhibit glioma invasion and decrease therapeutic resistance.